CONTENT ANALYSIS OF ORGANIC CLAIM FOOD ADVERTISEMENT ON YOUTUBE - Hanan Anisa Saniyah; Ujang Sumarwan (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Advertisements with organic claims must be able to be proven by how the product is made, the ingredients used, and legal organic certification. Providing correct information is a form of consumer education and protection. This study aims to analyze video advertisements of organic food claims on YouTube social media. The results of the analysis are adjusted in fulfillment of the Consumer Protection Law (UUPK) Number 8 of 1999. This research analyzes the variables of product characteristics, video characteristics, advertising characteristics, and organic claims using the content analysis method and exploratory design. The sample selection was carried out using purposive sampling technique with certain characteristics. The research sample is 200 organic claim advertising videos on YouTube. Data were collected and processed using Microsoft Excel, SPSS 25.0, and Voyant. The results of the analysis show that 62,5 percent of ads use subjective claims and 64,5 percent of ads do not have organic certification. There were 91,5 percent of ads that violated article 17 and 29,0 percent of ads that violated the Ethics of Indonesian Advertising (EPI). Consumers need to improve their knowledge and understanding of organic claim advertisements and be careful in deciding product purchases.